Performance Optimization of the General Criminal Unit of Grobogan Police Satreskrim in Revealing Motor Vehicle Theft to Actualize Professional Law Enforcement (Advances in Police Science Research Journal, 2024)
The task of law enforcement carried out by the National Police is often damaged by the poor performance of its individuals in handling incoming reports or complaints of crime, resulting in many reports which then result in a decrease in the number of disclosures of criminal acts. This also happened at the Grobogan Police Station, where in the last four years there has been a decline in the settlement of criminal acts, especially in the vehicle theft case, even though organizational resources in the form of human resources, budget and infrastructure, as well as the mechanism for carrying out the duties of the Grobogan Police Criminal Investigation Unit have been available. This study aims to analyze the organizational resources and mechanisms used by the Criminal Investigation Unit of the Grobogan Police in uncovering vehicle theft that occurred. The research method uses a qualitative approach with the type of field research. Sources of data obtained from primary and secondary data sources. Data collection was carried out by interview, observation, and document study techniques. The research location is the Criminal Investigation Unit of the Grobogan Police. The validity of the data using the triangulation method. Data analysis was carried out using an interactive model through data reduction, data presentation, as well as conclusions and data verification. The results showed that the organizational resources used in disclosing the criminal act of theft did not meet the expected requirements both in terms of human elements, money, materials, methods and machines. In addition, problems were found in every stage of implementation, be it in planning, organizing, actuating, or supervising. Efforts to optimize the disclosure of criminal acts of theft are carried out by holding scheduled FGDs, gathering members of the criminal police ranks, planning a budget with a priority scale, targeting completion of at least 1 case 1 month, utilizing Cell Dump technology, activating the one person one file system, and utilizing the E-Manajemen Penyidikan application.
Keywords: Kinerja, Penyidikan dan Penyelidikan